2014
DOI: 10.3892/or.2014.3691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of the preoperative GSA index in 99mTc-GSA scintigraphy in hepatitis C virus-related hepatocellular carcinoma

Abstract: Abstract. We aimed to examine the relationship between the preoperative GSA index [uptake ratio of the liver to the liver plus heart at 15 min (LHL15) to uptake ratio of the heart at 15 min to that at 3 min (HH15) ratio] calculated from 99m Tc-labeled diethylene triamine pentaacetate-galactosyl human serum albumin ( 99m Tc-GSA) scintigraphy and background liver fibrosis and to investigate whether the GSA index can be a useful predictor in hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, we previously reported that the GSA index as defined by the uptake ratio of the liver to the liver plus heart at 15 min to the uptake ratio of the heart at 15 min to that at 3 min ratio calculated from 99mTc-labeled diethylene triamine pentaacetate-galactosyl human serum albumin (99mTc-GSA) scintigraphy yielded the highest area under the receiver operating curve (AUROC) for predicting histologically proven cirrhosis with a level of 0.786 at an optimal cut-off value of 1.37 (sensitivity: 65.9%; specificity: 79.0%) in HCV-related HCC patient treated with surgical resection (SR) ( n = 213) and it can be a useful predictor for HCC recurrence after surgery [ 32 ]. Furthermore, in non-B and non-C HCC patients treated with SR ( n = 118), we have shown that the FIB-4 index yielded the highest AUROC for histologically proven cirrhosis with a level of 0.887 at an optimal cut-off value of 2.97 (sensitivity: 92.3%; specificity: 69.6%), and FIB-4 index >2.97 ( P = 0.044) was a significant independent factor linked to HCC recurrence [ 33 ].…”
Section: Noninvasive Methods For Predicting Lc or Lc Related Complmentioning
confidence: 99%
“…On the other hand, we previously reported that the GSA index as defined by the uptake ratio of the liver to the liver plus heart at 15 min to the uptake ratio of the heart at 15 min to that at 3 min ratio calculated from 99mTc-labeled diethylene triamine pentaacetate-galactosyl human serum albumin (99mTc-GSA) scintigraphy yielded the highest area under the receiver operating curve (AUROC) for predicting histologically proven cirrhosis with a level of 0.786 at an optimal cut-off value of 1.37 (sensitivity: 65.9%; specificity: 79.0%) in HCV-related HCC patient treated with surgical resection (SR) ( n = 213) and it can be a useful predictor for HCC recurrence after surgery [ 32 ]. Furthermore, in non-B and non-C HCC patients treated with SR ( n = 118), we have shown that the FIB-4 index yielded the highest AUROC for histologically proven cirrhosis with a level of 0.887 at an optimal cut-off value of 2.97 (sensitivity: 92.3%; specificity: 69.6%), and FIB-4 index >2.97 ( P = 0.044) was a significant independent factor linked to HCC recurrence [ 33 ].…”
Section: Noninvasive Methods For Predicting Lc or Lc Related Complmentioning
confidence: 99%
“…Two papers compared survival rates in patients with liver function uptake values above or below a certain level (reported in the same column). Nishikawa et al [60] found a significant difference between survival rates in patients above and below a certain cut-off, whereas Yano et al [89] did not. Moreover, Rassam et al [67] did not find a significant association between 90-day mortality and the preoperative FLR function or uptake rate of [ 99m Tc]Tc-mebrofenin.…”
Section: Prediction Of Postoperative Mortalitymentioning
confidence: 96%
“…Kim et al [39] found LHL15 to be a significant predictor of overall complications, including mortality, in multivariate analysis. Nishikawa et al [60] found the GSA index to be a significant predictor of recurrence-free survival and overall survival in univariate analysis and documented a significant predictive value of the GSA index for recurrence-free survival in multivariate cox regression analysis (hazard ratio (HR) 2.4, p < 0.001). However, Yano et al [89] found that the GSA-R max parameters were not associated with overall survival or tumor-free survival in multivariate cox regression analysis, and Yamao et al [87] did not find a significant association between LHL15 and overall survival in univariate cox regression analysis.…”
Section: Prediction Of Postoperative Mortalitymentioning
confidence: 99%